An Analysis of the Impact of Healthcare Workforce, Educational Infrastructure, and Non-Food Expenditure on Human Development Index (HDI) in Humbang Hasundutan Regency, Indonesia - Hutabarat, Pomer Morjut; Lubis, Satia Negara; Purwoko, Agus (CV. ARGA FARMA, 2024)
This study aims to analyze the impact of healthcare workforce, educational infrastructure, and non-food per capita expenditure on the Human Development Index (HDI) in Humbang Hasundutan Regency, North Sumatra, Indonesia. Using time-series data from 2005 to 2022 and applying multiple linear regression analysis through SPSS 26, the research finds that both healthcare workforce and educational infrastructure significantly and positively influence the HDI. However, non-food per capita expenditure does not exhibit a significant effect on the HDI. These findings suggest that improvements in healthcare and education are pivotal in driving human development in the region. Policymakers are advised to focus on strengthening these key sectors to ensure sustained socio-economic growth. The study contributes to the existing literature on human development by providing region-specific insights and emphasizes the importance of tailored policy interventions for improving HDI at a local level.